Construction of the control algorithm to improve energy efficiency of a switched reluctance electric motor - А. V. Kashuba; A. V. Shevkunova (Омский научный вестник)
An energy-efficient switched reluctance electric drive is considered in relation to electric rolling stock. It fully meets such requirements as good adjustment properties, high energy efficiency and operational reliability. The scientific and technical value of the results of the work lies in the development of an algorithm for controlling a traction switched reluctance motor that reduces the operating current while providing the necessary power. The calculations are made by means of specialized programs interacting with each other FEMM and MATLAB. The materials of this study are of practical value for improving the operational and technical and economic indicators of electric rolling stock.